2012
DOI: 10.1103/physrevc.86.031304
|View full text |Cite
|
Sign up to set email alerts
|

Description of158Er at ultrahigh spin in nuclear density functional theory

Abstract: Rotational bands in 158 Er at ultra-high spin have been studied in the framework of relativistic and non-relativistic nuclear density functional theories. Consistent results are obtained across the theoretical models used but some puzzles remain when confronted with experiment. Namely, the many-body configurations which provide good description of experimental transition quadrupole moments and dynamic moments of inertia require substantial increase of the spins of observed bands as compared with experimental … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 32 publications
(52 reference statements)
3
31
0
Order By: Relevance
“…Therefore, before computing the Routhians as functions of the tilting angle, we first performed extensive PAC calculations so as to determine deformations of various minima. Similar to the PAC calculations in 158 Er [24], we found that the configurations generally have three typical deformations, namely, (Q t , γ) ∼ (9 eb, 9…”
Section: Tests Of the Ko Conditions Insupporting
confidence: 82%
See 1 more Smart Citation
“…Therefore, before computing the Routhians as functions of the tilting angle, we first performed extensive PAC calculations so as to determine deformations of various minima. Similar to the PAC calculations in 158 Er [24], we found that the configurations generally have three typical deformations, namely, (Q t , γ) ∼ (9 eb, 9…”
Section: Tests Of the Ko Conditions Insupporting
confidence: 82%
“…Recently, a multitude of high-spin bands in nuclei around 158 Er have been observed [14][15][16][17][18][19][20] and interpreted in terms of triaxial strongly deformed (TSD) structures predicted by the PA cranking (PAC) calculations [14,[21][22][23][24]. Specifically, in 158 Er, two minima (dubbed TSD1 and TSD2) with similar β 2 and |γ| deformations, but opposite signs of γ, are calculated to be separated by a pronounced barrier.…”
Section: Introductionmentioning
confidence: 99%
“…It represents the realization of covariant density functional theory (CDFT) for rotating nuclei with no pairing correlations [43]. It has successfully been tested in a systematic way on the properties of different types of rotational bands in the regime of weak pairing such as normal-deformed [53], superdeformed [52,54], as well as smooth terminating bands [43] and the bands at the extremes of angular momentum [55].…”
Section: The Details Of the Theoretical Calculationsmentioning
confidence: 99%
“…It is globally tested for ground state observables in eveneven nuclei [67] and systematically tested for physical observables related to excited states in heavy nuclei [57,68,69]. The CRMF and CRHB calculations with the NL3* CEDF provide a very successful description of different types of rotational bands [55,57,66] both at low and high spins.…”
Section: The Details Of the Theoretical Calculationsmentioning
confidence: 99%
“…The successes of the CDFT in the description of rotating nuclei both in paired and unpaired regimes and at different extremes (superdeformation [see Ref. [10] and references therein], ultrahigh spins [29] and the limits of angular momentum in nuclear configurations [10,30]) are well documented.…”
Section: Introductionmentioning
confidence: 99%